MRP(Material Requirement Planning) Applications In Industry-A REVIEW - Raqeyah Jawad Najy (IJRDO - Journal of Business Management, 2020)
Material requirements planning (MRP) is a production planning and inventory management system used to manage logistics processes and designed to assist production managers in scheduling and placing orders for items of dependent demand. If it is implemented and used properly, it can be helpful for production managers to plan capacity needs and allocate production time. The article provides characteristics of the mentioned method; it describes the possible areas of application in manufacturing, purchasing and delivering activities. The paper considers the analysis of the production logistics in the chosen industrial company, focusing on information MRP system and the bottlenecks in the production. The work is a part of subject review about MRP applications in industrial companies.